Status and trends of medical certification of cause of death in India: insights from the 2020 annual report - Kumar, Harish Kumar Mohan; Thulasimani, Ilaiyabharathi; Manikgantan, Sargema; Kumar Raju, Mohan (International Journal Of Community Medicine And Public Health, 2025)
Background: Accurate cause-of-death data are essential for public health planning and disease surveillance. In India, the Medical Certification of Cause of Death (MCCD) system faces persistent challenges, including low coverage, regional disparities, and data quality issues. We aimed to assess the extent of medical certification, demographic patterns, and cause-specific mortality using data from the 2020 national MCCD report. Methods: We conducted a descriptive secondary data analysis using the 2020 MCCD report published by the Office of the Registrar General, India. We examined medically certified deaths by state, sex, age group, and place of occurrence. We also evaluated cause-of-death patterns and compared findings with previous years and related national datasets. We used descriptive statistics to analyse certification coverage, demographic patterns, and cause-specific mortality. Results: In 2020, India registered 8.1 million deaths, of which only 1.81 million (22.5%) were medically certified. Certification rates ranged widely, from 100% in Goa and Manipur to below 7% in Bihar, Jharkhand and Madhya Pradesh. Urban and institutional deaths accounted for over 85% of certified cases, and 64% of certified deaths occurred among males. Circulatory diseases were the leading cause (32.1%), followed by respiratory diseases (10%) and COVID-19 (8.9%). Ill-defined causes comprised 10.6% of certified deaths, highlighting diagnostic and reporting gaps. Conclusions: MCCD system remains skewed toward urban, institutional, and male-dominated reporting, limiting its effectiveness. Strengthening the system through digitization, standardized physician training, and rural outreach is essential to improve the coverage and accuracy of mortality data in India.